Pregnancy with choriangioma: a placental disorder that causes fetal death - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Ni Komang Anik Pirgantari; Made Diah Vendita Sakuntari; Ni Wayan Dewi Purwanti; NI Putu Nining Gianni; Ni Luh Made Diah Mas Cahyani Putri; Ni Luh Md Dwi Laxmi Satriani; Firsta Sesarina Mintariani; Anak Agung Wahyu Putri Agustini (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2022)
Introduction: Chorioangioma is the most common non-trophoblastic vascular tumor of the placenta. It was estimated that the incidence of chorioangioma was 1%. Although the incidence was not widely large, it has high mortality and morbidity. Commonly, chorioangiomas is a small asymptomatic lesion found only after birth after careful excision of the placenta. In making it easier to visualize the food vessels entering the placental mass and peritumoral diffuse vasculature we could use the color doppler. The wide range of outcomes and limited studies related to this case makes it quite difficult to handle. Thus, this study aimed to provide information on chorioangioma from diagnosis to the management. Case description: Mother A is our referral patient who was recommended to do an ultrasound, with a diagnosis of 20 weeks gestation with suspected IUFD and a cyst in the placenta measuring 6.5cm x 4.1cm x 5.4 cm, the mother has not felt fetal movement. Ultrasound examination revealed a hematoma at the time of insertion of the umbilical cord in the placenta. The location of the placenta in the corpus anterior grade 1. No heartbeat was found in the baby, and the baby's weight was 529 grams. Conclusion: The adverse outcome is known to be associated with chorioangioma. It depends on the mass size, and the existence of fetal hydrops. The worst prognosis that we found in this case was no heartbeat when the baby was born.